Analysis of haloarchaeal twin-arginine translocase pathway reveals the diversity of the machineries. Issue 5 (May 2019) - Ghosh, Deepanjan; Boral, Debjyoti; Vankudoth, Koteswara Rao; Ramasamy, Sureshkumar
Abstract: The twin-arginine translocase (Tat) pathway transports folded proteins across the plasma membrane and plays a critical role in protein transport in haloarchaea. Computational analysis and previous experimental evidence suggested that the Tat pathway transports almost the entire secretome in haloarchaea. The TatC, receptor component of this pathway shows greater variation in membrane topology in haloarchaea than in other organisms. The presence of a unique fourteen-transmembrane TatC homolog (TatCt ) in haloarchaea, over and above the expected TatC topological variants, indicates a strong correlation between the additional homologs and the large number of substrates transported via the haloarchaeal Tat pathway. Various combinations of TatC homologs with different topologies—TatCo, TatCt, TatCn, and TatCx have been observed in haloarchaea. In this report, on the basis of these combinations we have segregated all haloarchaeal Tat substrates into two groups. The first group consists of substrates that are transported by TatCt alone, whereas the second group consists of substrates that are transported by the other TatC homologs (TatCo, TatCn, and TatCx ). The various haloarchaea TatA components also shows the possible segregation towards the substrates. We have also identified the possible homologs for Tat substrate chaperones, which act as a quality-control mechanism for proper protein folding. Further sequence analysis implies that the two TatC domains of TatCt complement each other's functionally. Substrate analysis also revealed subtle differences between the substrates being transported by various homologs: further experimental analysis is therefore required for better understanding of the complexities of the haloarchaeal Tat pathway.